W-Band GaAs pHEMT Power Amplifier MMIC Stabilized Using Network Determinant Function - Seong-Hee Han; Dong-Wook Kim (Micromachines)
This paper presents a W-band power amplifier monolithic microwave integrated circuit (MMIC) that is designed for high-precision millimeter-wave systems and fabricated using a 0.1 µm GaAs pHEMT process. The amplifier’s stability was evaluated using the network determinant function, ensuring robust performance under both linear and nonlinear conditions. Simultaneous matching for gain and output power was achieved with minimal passive elements. The developed power amplifier MMIC exhibits a linear gain exceeding 20 dB and an input return loss greater than 6 dB across the 88–98 GHz range. It delivers an output power of 23.8–24.1 dBm with a power gain of 17.3–17.9 dB in the 88–97 GHz range and achieves a maximum power-added efficiency (PAE) of 24% at 94 GHz.